Metabolomics and Transcriptomics Reveal the Effects of Different Fermentation Times on Antioxidant Activities of Ophiocordyceps sinensis - Min He; Tao Wang; Chuyu Tang; Mengjun Xiao; Xiaojian Pu; Jianzhao Qi; Yuling Li; Xiuzhang Li (Journal of Fungi)
Ophiocordyceps sinensis is a fungus that is cultured through fermentation from wild Chinese cordyceps. While studies have examined its metabolites, the evaluation of its antioxidant capacity remains to be conducted. The antioxidant results of O. sinensis indicate that the ferric ion-reducing antioxidant power (FRAP), antioxidant capacity (2.74 ± 0.12 μmol Trolox/g), 2,2-diphenyl-1-picrylhydrazyl (DPPH•) free radical scavenging rate (60.21 ± 0.51%), and the hydroxyl free radical scavenging rate (91.83 ± 0.68%) reached a maximum on day 30. Using LC-MS/MS to measure the metabolites on D24, D30, and D36, we found that the majority of the differential accumulated metabolites (DAMs) primarily accumulate in lipids, organoheterocyclic compounds, and organic acids and their derivatives. Notably, the DAMs exhibiting high peaks include acetylcarnitine, glutathione, linoleic acid, and L-propionylcarnitine, among others. The transcriptome analysis results indicate that the differentially expressed genes (DEGs) exhibiting high expression peaks on D30 primarily included lnaA, af470, and ZEB1; high expression peaks on D24 comprised SPBC29A3.09c and YBT1; high expression peaks on D36 included dtxS1, PA1538, and katG. The combined analysis revealed significant and extremely significant positive and negative correlations between all the DAMs and DEGs. The primary enriched pathways (p < 0.05) included glutathione metabolism, tryptophan metabolism, carbon metabolism, biosynthesis of secondary metabolites, and phenylalanine metabolism. The metabolic pathway map revealed that the DAMs and DEGs influencing the antioxidant activity of O. sinensis were significantly up-regulated on D30 but down-regulated on D36. The correlation analysis suggests that an increase in the content of DEGs and DAMs promotes an increase in the levels of enzyme and non-enzyme substances, ultimately enhancing the antioxidant capacity of O. sinensis. These findings serve as a reference of how DAMs and DEGs affect the antioxidant activity of O. sinensis. This may contribute to the enhanced development and application of O. sinensis.